Cutting Seton Fistulotomy for the Management of High Anal Fistula: Prospective Evaluation of Clinical Results in Yaoundé - Savom, Eric Patrick; Bwelle Motto, Georges Roger; Bang, Guy Aristide; Ekani Boukar, Mahamat Yannick; Guifo, Marc Leroy; Essomba, Arthur (HEALTH SCIENCES AND DISEASE, 2016)
Background. High anal fistulas require multiple operations and the use of sphincter sparing techniques. All these are expansive for patients living in developing countries like ours. Thus, the use of cutting seton is the main surgical method practiced here. The objective of this study was to evaluate its clinical outcomes in high anal fistula. Patients and methods We conducted a prospective study of patients undergoing cutting seton fistulotomy for high anal fistula. Preoperative and postoperative evaluation included anamnesis, clinical examination and anuscopy. Fecal continence was assessed using the Pescatori continence score (0 to 6). Results We registered 19 high transsphincteric fistulas and 1 supratrasphincteric fistula. Nine patients reported varying degrees of earlier faecal incontinence. Their mean continence score decreased from 2.8 to 2.1 (p = 0.111). It decreased from 2 to 1.5 (p = 0.495) in the diabetic patients and increased from 2.3 to 3.3 (p = 0.225) in HIV+ patients while in HIV- patients, we noted an amelioration from 1.1 to 0.6 (p = 0.049). There was no difference between pre- and postoperative values of continence in fully continent patients, although 1 patient reported minor alterations of continence (Pescatori score = 2). Healing was achieved in 17 patients with 1 case of recurrence. Conclusion The use of cutting seton in high anal fistula is an effective technique. It improves continence in incontinent patients and respects that of continent patients with a long lasting resolution of the problem of suppuration.